Implementation of an LBE spallation target in an accelerator-driven molten salt subcritical reactor. Issue 8 (3rd August 2017) - Bak, Sang-In; Hong, Seung-Woo; Kadi, Yacine
ABSTRACT: An accelerator-driven system (ADS) combined with a subcritical molten salt reactor (MSR) is a type of hybrid reactor originally designed to use Th/U (or U/Pu ) fuel cycles. In most accelerator-driven molten salt reactor (AD-MSR) concepts, the salt material is also used as a target for inducing spallation neutrons. Although a neutron source is an important component in the design of ADS, only a few studies have addressed the effects of the neutron spallation source in the AD-MSR. Incidentally, there is no quantitative study on how much the beam power can be reduced by installing a spallation target in a sodium chloride-based fast reactor. We studied the proton and the neutron source efficiencies of an AD-MSR with chloride fuels by considering an Lead Bismuth Eutectic (LBE) spallation target. This LBE target is found to increase the proton source efficiency significantly. The required beam power for an AD-MSR can be reduced by 33 % and 16 % for NaCl-Th/ 233 U and NaCl-U/Pu fuels, respectively, relative to the AD-MSR without the LBE spallation target by keeping the same k eff . The energy gain can be increased up to 1.5 times and 1.2 times for NaCl-Th/ 233 U and NaCl-U/Pu fuels, respectively. Thus, incorporating a spallation target module in an AD-MSR can significantly reduce the burden on the accelerator.